THE EFFECT OF FERMENTATION TIME INOCULUM LEVELS OF Bacillus amyloliquefaciens ON NUTRITIONAL LEVELS OF PAITAN (TITHONIA DIVERSIFOLIA) - Montesqrit, -; Mirzah, -; Pratiwi, Shafira (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2022)
This study aims to determine the interaction between the duration of fermentation with the level of Bacillus amyloliquefaciens inoculum on the nutritional content of Mexico sunflowers (Tithonia diversifolia) leaves. The method used is an experimental method with a 3 × 3 factorial completely randomized design (CRD) with three replications. Factor A (inoculum level) consisted of A1 = 1%, A2 = 2% and A3 = 3%. Factor B (fermentation time) consisted of B1 = 1 day, B2 = 2 days and B3 = 3 days. The variables observed were dry matter (%), crude fibre (%), and crude protein content (%). The results showed no interaction between inoculum levels and fermentation time on all experimental parameters. Still, inoculum levels and fermentation time affected the crude protein and crude fibre content of Mexico sunflowers leaves. This study concluded that one-day fermentation with a level of 3% inoculum resulted in dry matter content of 46.73%, crude protein content of 26.40%, and crude fibre content of 7.88%. Keywords: Bacillus amyloliquefaciens, fermentation time, inoculum dose, nutritional content, Tithonia diversifolia leaf